Reduced Cardiovascular Mortality Associated with Early Vascular Access Placement in Elderly Patients with Chronic Kidney Disease - Lee, Timmy (Am J Nephrol, 2016)
BACKGROUND: Elderly patients with cardiovascular comorbidities are more likely to die before progressing to needing hemodialysis, so deferring their pre-dialysis vascular access (VA) surgery has been suggested. However, recent declines in cardiovascular mortality in the U.S. population may have changed this consideration. We assessed whether there has been a parallel decrease in cardiovascular co-morbidity in elderly chronic kidney disease (CKD) patients undergoing pre-dialysis access surgery, and whether this impacted clinical outcomes after access creation and cardiovascular events after hemodialysis initiation. METHODS: We identified 3,418 elderly patients undergoing pre-dialysis VA creation from 2004-2009, divided them into 3 time cohorts (2004-05, 2006-07 and 2008-09), and assessed their clinical outcomes during 2 years of follow-up. RESULTS: There was a progressive decrease in patients with history of peripheral vascular disease (66.5 to 59.7%, p<0.005), heart failure (47.0 to 35.8%, p<0.005), and myocardial infarction (6.5 to 3.3%, p<0.001) from 2004-2009. Death before hemodialysis decreased from 17.5 to 12.6%, survival without hemodialysis increased from 14.5 to 19.0%, and hemodialysis initiation remained constant at ~68% (p<0.001). The incidence of death or cardiovascular event in the first year of hemodialysis decreased from 2004-05 to 2008-09 (HR=0.83, 95% CI, 0.69-0.99; p=0.04). CONCLUSION: In the context of a changing population from 2004-09, a progressive decrease in cardiovascular comorbidities in elderly CKD patients undergoing pre-dialysis VA surgery was associated with a decrease in death before hemodialysis and cardiovascular events after starting hemodialysis. These insights should be translated into more thoughtful consideration of which elderly patients should undergo pre-dialysis access surgery.